Study on the Coupled Vibration of Transmission Shaft-rear Axle System based on Adams - Lin Zou; Yujun Lie; Bing Jia; Ao Qin; Jinli Xu (Jixie chuandong)
Taking the spider cardan shaft-hypoid gear pair-tapered roller bearing-half shaft rear axle of the shaft system as the research object， based on the dynamics analysis software Adams， considering the influence of the intermediate support， the transmission shaft-rear axle system dynamics simulation model is established. The second-order （angular） acceleration amplitude curves of the intermediate support， the inputting position of the rear axle and the end of the half axle at different input speeds are obtained. The peak value position of the second-order （angular） acceleration curve is also determined. By using the bench test study based on order tracking， the experimental results show the natural frequency of the first order torsional vibration of the system is 57 Hz， which is consistent with the modal frequency of the system obtained by simulation analysis， and proves the correctness of the Adams simulation calculation result of the transmission shift-rear axle system. The problem of low accuracy of dynamics simulation in studying the coupling vibration characteristics of the flexible transmission system， especially in obtaining the modal parameters is solved.